A preliminary study of regression calculation of the change–with–time parameter in the Cobb–Douglas production function. (4th August 2014) - Shicheng, Chen; Yingbao, Zhang
This paper introduces the regression method of the change with–time parameter in the Cobb–Douglas production function. It demonstrates that past results of this method are inaccurate because they use the α and β in the Cobb–Douglas production function, which although considered unchangeable are in fact variable. Further, we introduce a new method of getting annual labour output resilience coefficients, capital output resilience coefficients and the technology progress rate.